Effect of various beverages on adhesion of repaired CAD/CAM restorative materials - Yiğit, Elif; Güngör Erdoğan, Hamiyet; Eyüboğlu, Tan Fırat; Özcan, Mutlu (MDPI, 2023)
(1) Background: The purpose of this study was to determine the effect of commonly consumed beverages on the bond strength of three different computer-aided design-computer-aided manufacturing (CAD/CAM) resin-ceramic hybrid materials repaired with resin-based composite (RBC) materials. (2) Materials and Methods: Rectangular prism specimens (N = 138) measuring 6 mm x 5 mm x 2 mm were obtained from GC Cerasmart (GC), Lava Ultimate (LU), and Vita Enamic (VE) blocks. These blocks were polished and then subjected to thermal cycling (10,000 cycles, 5 & DEG;C to 55 & DEG;C). After the surface treatment was applied, the average surface roughness value was measured. All the surfaces were repaired with RBC. Thermal cycling was performed for the second time. Each group was then distributed into three subgroups according to the beverage used: tea (t), cola (c), and distilled water (0) (n = 15). The specimens were stored in these solutions for 28 days and then subjected to the shear bond strength (SBS) test. Statistical analysis was performed using a two-way ANOVA test with Bonferroni adjustment. (3) Results: The surface roughness of the materials presented no significant difference after different surface treatments (p > 0.05). No significant difference was observed among the materials (p > 0.05). Tea and cola presented similar SBS values (p > 0.05). Both were significantly lower than distilled water (p < 0.001, p < 0.001, respectively). (4) Conclusions: Consumption of beverages reduces the bond strength in surfaces repaired with RBC to CAD/CAM resin-ceramic hybrid materials. (5) Clinical Significance: Repairing damaged resin matrix dental restorations with RBC is advantageous in terms of time and cost by achieving adequate bond strengths. Frequently consumed beverages reduce the bond strength of repaired CAD/CAM resin-ceramic hybrid materials.
Keywords: Adhesion; Composite Resin; Dental Materials; Polymer Infiltrated Ceramic Network; Resin Matrix Ceramic; Resin Nanoceramic; Shear Bond Strength